An Evaluation of the organization, administration and operational set-up of the audio-visual centers of the regional normal schools of the Philippines - Calixto, Jeremias A. 1917- (s.n.], 1967)
This is an evaluation of the organizaton, administration, and operation of the audio-visual centers of eight Philippine regional normal schools. It delves on the nature of the above phases of the audio-visual program towards the achievement of the objectives.